Cranbury : A New Jersey Town from the Colonial Era to the Present - Chambers, John Whiteclay (Book collections on Project MUSE., 2012)
One of the oldest towns in New Jersey, Cranbury has a long and noteworthy history that is in part distinctive and in part broadly representative of larger themes in the development of the state and the nation. In this beautifully illustrated book sponsored by Cranbury Landmarks, Inc., historian John Whiteclay Chambers II links the narrative of this remarkable town to contemporary debates about suburbanization and urban planning.